#### Answer

$x^2-9x+14 = (x-2)~(x-7)$

#### Work Step by Step

Let's consider a trinomial in this form: $~x^2+bx+c$
To factor this trinomial, we need to find two numbers $r$ and $s$ such that $r+s = b$ and $r\times s = c$
Then we can factor the trinomial as follows:
$~x^2+bx+c = (x+r)~(x+s)$
Let's consider this trinomial: $~x^2-9x+14$
To factor this trinomial, we need to find two numbers $r$ and $s$ such that $r+s = -9$ and $r\times s = 14$. We can see that $(-2)+(-7) = -9~$ and $(-2)\times (-7) = 14$
We can factor the trinomial as follows:
$x^2-9x+14 = (x-2)~(x-7)$